2013
DOI: 10.1158/0008-5472.can-13-0518
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-Terminal Modulator Protein Positively Regulates Akt Phosphorylation and Acts as an Oncogenic Driver in Breast Cancer

Abstract: Akt activation has been implicated broadly in tumorigenesis, but the basis for its dysregulation in cancer cells is incompletely understood. In this study, we sought to clarify a regulatory role for the Akt-binding carboxy-terminal modulator protein (CTMP), which has been controversial. In evaluating CTMP expression in paired normaltumor specimens of 198 patients with breast cancer, we found that CTMP was upregulated in breast tumors, where it was associated with poor patient survival. Notably, CTMP expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…In contrast, CTMP had the opposite effect on neuroprotection after brain injury9, 14, 17, 42 and insulin resistance,15 via restraining AKT signaling. Notably, a few reports have suggested that CTMP directly binds to AKT through the N‐terminal domain 1 to 64 amino acids at the plasma membrane,16 enhances AKT phosphorylation,43 and functions as an oncogenic molecule in head and neck squamous cell carcinoma44 and breast cancer 16, 45. These findings challenge the association of CTMP with AKT's phosphorylation condition and functional effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, CTMP had the opposite effect on neuroprotection after brain injury9, 14, 17, 42 and insulin resistance,15 via restraining AKT signaling. Notably, a few reports have suggested that CTMP directly binds to AKT through the N‐terminal domain 1 to 64 amino acids at the plasma membrane,16 enhances AKT phosphorylation,43 and functions as an oncogenic molecule in head and neck squamous cell carcinoma44 and breast cancer 16, 45. These findings challenge the association of CTMP with AKT's phosphorylation condition and functional effects.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, accumulating evidence suggests that CTMP plays vital roles in numerous pathological processes, such as tumor,8, 12, 13 neuroprotection,14 and metabolism 15. Initially, CTMP has been determined to exert a complex influence in multiple cancers by regulating cell survival, proliferation, and angiogenesis 12, 13, 16. Moreover, mounting studies manifest that inhibition of CTMP would be beneficial in the neuroprotection in response to brain injury, no matter whether the subjects combined with diabetes mellitus or not 9, 14, 17.…”
Section: Introductionmentioning
confidence: 99%
“…This finding comes in agreement with the literature data that mention an over-expression of carboxyl terminus on the carcinoma cell. 3 The HA component is predominantly localized near the cell membrane. At a certain focal plane in the interior of the cell, the Raman images (insets Figure 5, A and B) evidence that the AuHA sensors are localized at the edge of the cell and not in the cytosol.…”
Section: Electrochemical Evidence Of Auha Sensor Interaction With -Coohmentioning
confidence: 99%
“…The binding site of this terminus is involved in glucose transport and glycogen synthesis. [1][2][3] Its overexpression enhances the glucose transport activity, glycogen and insulin synthesis 4 and tumorgenesis processes. 3 Numerous enzymatic pathways are also initiated at the carboxyl end of the plasma proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation